The effect of listening to binaural beats on frontal EEG alpha and beta of males and females / Haryanti Norhazman … [et al.] - Norhazman, Haryanti; Mohamad Zaini, Norliza; Tain, M. N.; Othman, Kama Azura; Jailani, Rozita; Omar, H. A. (Penerbit UiTM (UiTM Press), 2015)
Healthy brain is important in making sure that our lives are run properly. In most cases, normal and emotionally stable persons can think wisely and most of the time they are able to execute proper strategy in any problem solving. Listening to the Binaural Beats tone is one of the methods to distress. The effects of the Binaural Beats tone on male and female were observed on Alpha and Beta sub bands in both hemispheres. 40 subjects were involved in EEG data collection of sessions before and after listening to the binaural beats. The frequency of the beats used in this research is Alpha frequency of 9 Hz. The Energy Spectral Density feature (ESD)for both left and right hemispheres were used. Graphical analysis observing the box plot from the Normality Test shows that in session before, females have higher alpha level in both hemispheres as compared to males. Females have lower beta level in both hemispheres as compared to males. In session after listening to the binaural beats, both males and females have better decrement in beta levels in both hemispheres. Decrement in Beta sub bands also indicates that the subjects are getting more relaxed. The results indicate that male's brain is easier to be entrained. During listening to noise, female group shows that they are easily affected by noise as compared to males.